2018
DOI: 10.1029/2018wr023011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pollutant Source for Super‐Diffusion in Aquifers and Rivers with Bounded Domains

Abstract: Backward models for super‐diffusion in infinite domains have been developed to identify pollutant sources, while backward models for non‐Fickian diffusion in bounded domains remain unknown. To restrict possible source locations and improve the accuracy of backward probabilities, this technical note develops the backward model for super‐diffusion governed by the fractional‐divergence advection‐dispersion equation (FD‐ADE) in bounded domains. The resultant backward model is the fractional‐flux advection‐dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Theoretical justifications for the space-dependent transport parameters in almost all of the state-of-the-art, nonlocal transport models were articulated in Zhang et al 40 We will also test these hypotheses in Section 3. It is also noteworthy that eq 1a can be obtained by adding the subdiffusive term to the space fADE proposed by Zhang et al 7 A detailed derivation of this equation is also shown in Section S.1.4.…”
Section: Methodology Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical justifications for the space-dependent transport parameters in almost all of the state-of-the-art, nonlocal transport models were articulated in Zhang et al 40 We will also test these hypotheses in Section 3. It is also noteworthy that eq 1a can be obtained by adding the subdiffusive term to the space fADE proposed by Zhang et al 7 A detailed derivation of this equation is also shown in Section S.1.4.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…For example, eq 1a is analogous to the fractional-order advection−dispersion−reaction equation. 41 The nonlocal diffusive flux in eq 1d captures the contribution of diffusive flux from all upstream zones to the right (outlet) boundary due to nonlocal superdiffusive transport in the model domain [L, R] (see also Zhang et al 7 ), while the flux in eq 1c defines input of pollutant flux from outside the model domain, which is usually zero. In addition, the factor b and other parameters in eq 1a define the transport model: when b = 0, λ = 0, and κ = 0, model (1a) reduces to the standard spatiotemporal fractional-derivative model; 42 when b = 1, λ = 0, and α = 2, eq 1a reduces to the fractal mobile−immobile transport model (for the total phase) proposed by Schumer et al; 43 when b = 1, λ → ∞, and α = 2, eq 1a reduces to the classical advection−dispersion equation (ADE) with a retardation factor of 1 + β.…”
Section: Methodology Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the super‐diffusive jumps follow the main flow direction and the up‐location and upstream zones overlap each other (Zhang et al 2016). Therefore, the positive Riemann‐Liouville fractional derivative should be applied to describe the diffusive flux (Zhang et al 2016, 2018) because the positive fractional derivative in the s‐FADE model signifies that the diffusive flux of the contaminant source comes from the up‐location (Zhang et al 2016). According to the above debate, the one‐sided s‐FADE with a positive fractional derivative was used in this study.…”
Section: Methodsmentioning
confidence: 99%